EFFECT OF IMMUNOGLOBULIN Y PURIFIED FROM IMMUNIZED HEN EGGS ON THE GROWTH OF STAPHYLOCOCCUS AUREUS - Ali A. Al-Edany (Basrah Journal of Veterinary Research)
A novel purification method of egg yolk immunoglobulin (IgY) based on precipitation using agar-PEG was developed. This method was compared with chloroform extraction and polyethylene glycol (PEG) precipitation methods. The results showed the protein contents were high with chloroform method followed by agar-PEG then PEG method. The purity of resultant IgY was homogeneous with agar- PEG method followed by PEG method then chloroform extraction method. The IgY purified by agar –PEG method, obtained from hens immunized by formalin-treated S. aureus, showed a significant reduction in bacterial growth and the growth inhibition was dependent on specific-IgY concentration